Government Enterprise Architecture for Big and Open Linked Data Analytics in a Smart City Ecosystem - Lněnička, Martin; Máchová, Renáta; Komárková, Jitka; Pásler, Miroslav (Springer International Publishing AG, 2017)
Opening up government data introduces a change about how governments operate and how stakeholders use data. At the same time, the large amounts of data need to be collected, processed, transmitted, and published with the aim of enhancing the quality of urban life. Now, these trends are shaping smart cities efforts in the public sector. This paper aimed to clarify the concepts of enterprise architecture, big and open linked data analytics, and smart city and how they are related to each other. A conceptual framework was proposed to analyze the requirements of BOLD analytics in a smart city ecosystem. This was contextualized by decomposing selected smart city architectures that served as a basis for understanding the interrelationships between components. This framework can be used as a guide to help developers and designers in creating government enterprise architectures for BOLD analytics in smart cities.
Podniková architektura veřejné správy pro analýzu big a open linked dat v ekosystému chytrého města
Keywords: government enterprise architecture; big and open linked data; data analytics; smart city ecosystem; conceptual framework; podniková architektura veřejné správy; big a open linked data; analýza dat; ekosystém chytrého města; konceptuální rámec